STUDY THE EFFECT OF DIFFERENT CONCENTRATION OF SOLUBLE OZONE IN TWO KIND OF PATHOGENIC BACTERIA & TWO KIND OF PATHOGENIC FUNGI ASSOCIATED WITH SKIN INFECTIONS IN VITRO - Salih, Duha; Habib, Khalid; Rezoqe, Nada (Iraqi Journal of Science, 2024)
This preliminary in vitro study was conducted to investigate the effect of ozonated water on certain microorganisms (Bacteria&fungi) associated with wound & burn infection by using different concentrations of ozonated water (20,40 and 60 μg/ml) on these microorganisms .The results revealed that the percentages of inhibition were (10,20 &40%) for Staphylococcus aureus , (0,15&30%) for Pseudomonas aeruginosa and (25,50&65%) for Trichophyton mentagrophytes and finally (20,40 &60 %) for Candida albicans . Results also indicated that the percentages of inhibition were increased when we using more volume of ozonated water at concentration 60 μg/ml , in which all the microorganisms in this study inhibited completely when the volume of ozonated water used was 12ml , While the percentages of inhibition for T.mentagrophytes reached 95% only even when the volume of ozonated water used was 12 ml at concentration 60 μg/ml.